2017
DOI: 10.1080/10408398.2016.1231168
|View full text |Cite
|
Sign up to set email alerts
|

Absorption, metabolism, anti-cancer effect and molecular targets of epigallocatechin gallate (EGCG): An updated review

Abstract: Green tea is one of the most popular beverages in the world, especially in Asian countries. Consumption of green tea has been demonstrated to possess many health benefits, which mainly attributed to the main bioactive compound epigallocatechin gallate (EGCG), a flavone-3-ol polyphenol, in green tea. EGCG is mainly absorbed in the intestine, and gut microbiota play a critical role in its metabolism prior to absorption. EGCG exhibits versatile bioactivities, with its anti-cancer effect most attracting due to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
210
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 354 publications
(215 citation statements)
references
References 167 publications
3
210
0
2
Order By: Relevance
“…studied the absorption rate of four different kinds of monomeric proanthocyanidins in human subjects and found that the resulting plasma levels at 2 and 4 hr after consumption were ranked as follows: (−)‐EC > (+)­C = (+)­EC > (−)­C, and found 3’‐ O ‐methylated and 4’‐ O‐ methylated metabolites (Ottaviani et al., ). Similar results could also be found in other monomeric proanthocyanidins, such as EGCG (Gan, Li, Sui, & Corke, ; Takagaki & Nanjo, ). However, epi‐isomers might not always be easier to be absorbed compared with non‐epi‐isomers.…”
Section: Molecular Propertiessupporting
confidence: 79%
See 1 more Smart Citation
“…studied the absorption rate of four different kinds of monomeric proanthocyanidins in human subjects and found that the resulting plasma levels at 2 and 4 hr after consumption were ranked as follows: (−)‐EC > (+)­C = (+)­EC > (−)­C, and found 3’‐ O ‐methylated and 4’‐ O‐ methylated metabolites (Ottaviani et al., ). Similar results could also be found in other monomeric proanthocyanidins, such as EGCG (Gan, Li, Sui, & Corke, ; Takagaki & Nanjo, ). However, epi‐isomers might not always be easier to be absorbed compared with non‐epi‐isomers.…”
Section: Molecular Propertiessupporting
confidence: 79%
“…showed that 9.55 µmol (–)‐EC and the derivatives were recovered in human urine during 48 hr after they ingested 387.58 µmol of (–)‐EC measured by UHPLC‐ESI‐MS/MS without deconjugating enzymes (Castello et al., ). Another monomeric proanthocyanidins, EGCG with an extra group of gallic acid and larger Mw, showed an absorption rate of 0.012% in fasted rats and 0.32% in human plasma in 1 hr without using deconjugating enzymes in the study (Gan et al., ; Kale et al., ). A recent systematic review by Hu et al.…”
Section: Absorption and Digestion Of Proanthocyanidinsmentioning
confidence: 99%
“…Chen components, including EGCG, inhibited normal rat neurosphere adhesion and migration [61]. EGCG has pleiotropic activity on multiple cellular targets, both genetic and epigenetic (including DNA methyltransferase, NFκB, AMPK signaling pathway) [62][63][64]. It can act on its target with very impressive sensitivity, KD of 39.9 nM for the 67 Kd laminin receptor [65].…”
Section: Egcgmentioning
confidence: 99%
“…EGCG is represented by the most bioactive flavone-3-ol phenolic compound, this can be attributed to their eight free hydroxyl groups, responsible for the high versatile biological role [32]. The substitution with a methoxyl leads to a reduced antioxidant effect in the case of anthocyanidins compounds.…”
Section: Antioxidant Benefits Of Phytochemicalsmentioning
confidence: 99%